Effect of initial switch-on within 24 hours of cochlear implantation using slim modiolar electrodes - Woongsang Sunwoo (Nature Portfolio, 2021)
Abstract Reducing electrode impedance is an important factor in improving the functional benefits of cochlear implants (CIs). The immediate effect of early switch-on within 24 h of surgery on impedance among CI recipients with various types of electrodes has been reported previously; however, the immediate change and the evolution of electrode impedances of slim modiolar electrodes after early switch-on within 24 h of implantation has not. Therefore, the focus of this retrospective cohort study of CI patients was to compare the effect of early switch-on (n = 36) and conventional switch-on (n = 72) 2–4 weeks post-operation on impedance. Compared with impedance measured intraoperatively, our results demonstrate a significant decrease in impedance from 11.5 to 8.9 kΩ (p < 0.001) at 2–4 weeks after implantation in the early switch-on group, which sharply contrasted with elevated impedance values for conventional switch-on 2–4 weeks after implantation (from 10.7 to 14.2 kΩ, p = 0.001). Notably, a comparatively lower impedance than the conventional switch-on protocol was observed for up to 2 months post-operation. Most importantly, a much earlier stabilization of impedance can be achieved with the early switch-on protocol coupled with the slim modiolar electrode array compared to the conventional switch-on protocol, offering the advantage of reducing the number of required mapping sessions in the early stages of rehabilitation.